Political Exclusion, Oil, and Ethnic Armed Conflict. (December 2016) - Asal, Victor; Findley, Michael; Piazza, James A.; Walsh, James Igoe
Why do members of some ethnic groups rebel against the state? One approach holds that groups subject to exclusion from national politics engage in armed conflict. We theorize that the presence of resource wealth moderates the effect of political exclusion. Ethnic groups subject to exclusion whose settlement area includes oil wealth are more likely to experience the onset of armed conflict than groups experiencing exclusion alone. We depart from the convention of cross-national analysis to examine subnational, geocoded units of analysis—ethnic group settlement areas—to better capture the impact of natural resource distribution. Using data on ethnic group political exclusion derived from the Ethnic Power Relations database and geo-coded indicators, we conduct a series of logistic regression analyses for the years 1946 to 2005. We find that exclusion alone increase the likelihood of conflict, while the presence of oil wealth further raises the risk of war.